2020
DOI: 10.3390/brainsci10060369
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Mechanisms of Cognitive Impairment and Neurodegeneration by Toxoplasma gondii Infection

Abstract: Toxoplasma gondii is an obligate intracellular parasite considered one of the most successful pathogens in the world, owing to its ability to produce long-lasting infections and to persist in the central nervous system (CNS) in most warm-blooded animals, including humans. This parasite has a preference to invade neurons and affect the functioning of glial cells. This could lead to neurological and behavioral changes associated with cognitive impairment. Although several studies in humans and animal models have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 123 publications
0
28
0
Order By: Relevance
“…All of these factors lead to the imbalance of dopaminergic metabolism pathway. Moreover, the fact that anomalous accumulation of dopamine between synapses could cause various pathological processes such as increased dopamine concentration, synaptic structure disorder, proliferation of neural progenitor cells, and migration of neuron cells (Ortiz-Guerrero et al, 2020), thus may lead to the occurrence of psychiatric behavioral disorders. Alsaady et al (2019) also found that T. gondii could regulate the expression of dopamine b-hydroxylase (DBH) gene, which is responsible for dopamine synthesis of NE, resulting in a decrease in NE concentration in human/rat neurons that were cultured in vitro and were infected with tachyzoites, but the decrease in NE in rat brain tissue was limited in males.…”
Section: Dopamine-norepinephrine Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…All of these factors lead to the imbalance of dopaminergic metabolism pathway. Moreover, the fact that anomalous accumulation of dopamine between synapses could cause various pathological processes such as increased dopamine concentration, synaptic structure disorder, proliferation of neural progenitor cells, and migration of neuron cells (Ortiz-Guerrero et al, 2020), thus may lead to the occurrence of psychiatric behavioral disorders. Alsaady et al (2019) also found that T. gondii could regulate the expression of dopamine b-hydroxylase (DBH) gene, which is responsible for dopamine synthesis of NE, resulting in a decrease in NE concentration in human/rat neurons that were cultured in vitro and were infected with tachyzoites, but the decrease in NE in rat brain tissue was limited in males.…”
Section: Dopamine-norepinephrine Hypothesismentioning
confidence: 99%
“…However, brain cysts have been confirmed to cause persistent infection of nerve cells such as astrocytes, neurons, and microglia ( Courret et al., 2006 ). In fact, brain cysts could damage neurons, change the concentration of neurotransmitters, and interfere with the process of neuroimmune regulation in the host ( Ortiz-Guerrero et al., 2020 ). Infected mice with cerebral cysts burden showed significant behavioral disorders like diminished exploratory activity ( Barbosa et al., 2020 ), and the neurological and behavioral abnormalities are progressive and persistent in chronically infected mice that acquired primary infection in early adulthood ( Hermes et al., 2008 ).…”
Section: The Physiological Basis Of These Psychiatric and Behavioral ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it was concluded that chronic T. gondii infection can induce microglial proliferation in the brains of mice with progressed Alzheimer's disease, a promising approach for the treatment of this neuropathy [84]. In conclusion, the relationship of T. gondii and the development of Alzheimer's disease and cognitive impairment require further studies on human subjects and animal models [85] to elucidate the possible role of toxoplasmosis in the etiology of Alzheimer's disease.…”
Section: Toxoplasmosis and Parkinson's And Alzheimer's Neuropathiesmentioning
confidence: 99%
“…Additionally, owing to the immature status of the immune system in the fetus and neonates, congenital T. gondii infections may result in blindness, severe neurological sequelae, and even death [24]. Moreover, there is mounting evidence correlating latent toxoplasmosis to altered behavior, as well as the development and/or exacerbation of neurodegenerative diseases and sudden-onset psychoses, such as risk-taking/reckless behavior, bipolar disorder, depression, schizophrenia, and Alzheimer's disease [25][26][27]. Thus, the vast range of susceptible hosts and multiple routes of transmission render T. gondii one of the most successful pathogens on Earth, posing an immense threat to human health.…”
Section: Introductionmentioning
confidence: 99%